Perancangan Sistem Penentuan Kualitas Lingkungan Kerja Berdasarkan Multy Parameter Input Menggunakan Metode Mamdani Fuzzy Inferensi System (FIS): Design of a System for Determining the Quality of the Work Environment Based on Multi Parameters Input Using the Mamdani Fuzzy Inferenence System (FIS) Method - Nurahmad Hadi Cahyadi; Vanny Nastiti; Anugerah Ekha Gusti Audryadmaja; Denny Oktavina Radianto (LPPM STIKES Guna Bangsa, 2023)
The work environment has the potential for Occupational Diseases which cause health problems for workers due to physical work environment factors. The physical work environment is in the form of infrastructure conditions, temperature, lighting and noise, while the non-physical work environment is related to work relations and communication. Workers have the right to work in a safe and comfortable working environment because it is the main factor in determining worker conditions. A supportive work environment can trigger workers to increase productivity. The purpose of this study was to determine the comfort level of a workplace using three variables, namely temperature, lighting and noise with the Mamdani Fuzzy Inference System (FIS) approach. Using the Mamdani FIS method and Matlab R2010b program, it is expected to measure the condition of the work environment, including temperature, lighting, and noise, so that if the work environment conditions are inadequate, evaluation and improvement can be carried out. This research was carried out by a system engineering to determine the quality of the workplace environment using the Mamdani FIS method algorithm through the matlab software. It has been assumed that there are three indicator variables used to determine a condition in which each variable has its own decomposition of the input function and fuzzy set. Based on the case study used as a sample, the room conditions had a temperature level of 22Â°C, 55 db of noise and 210 lux of lighting, which resulted in an environmental quality of 91.3 with good workspace criteria.